Germinação e conservação de sementes de Balfourodendron riedelianum (Engler) Engler - Ignácio, Vanessa Leonardo (2013)
The growing awareness of society to ecological problems is providing a considerable increase in demand for seeds and seedlings of native species. The Balfourodendron riedelianum (Engler) Engler is a native woody species of economic importance and ecological landscape, popularly known as ivory wood. The purpose of this study was to identify the ideal temperature for germination and determine the seed physiological potential of this species collected from different sources. The objective also their behavior with respect to storage and predict the storage period seeds and determine the constants of the longevity equation. Seeds collected in Marechal Cândido Rondon, Entre Rios do Oeste and Diamonte D'Oeste / PR were studied. For germination evaluation, two temperatures, 25 oC and 20-30 oC constant alternating with a photoperiod of 16-8 hours, and as substrate germitest paper were used. It was stored for 360 days, fruit in two different packaging (bag Kraft paper and glass) and in two different environments (controlled and uncontrolled). The experimental design used was completely randomized. The evaluated variables were: fruit length, percentage of germination, first count of germination, germination velocity index, moisture content, weight of thousand fruit and seedling length. Storage periods were 0, 90, 180, 270 and 360 days after fruit processing. For the development of the equations of longevity it was determined constants that made the equation through regression lines. The germination seeds of Balfourodendron riedelianum (Engler) Engler, was not affected by constant temperature of 25 oC compared with temperatures of 20-30 oC. The seedling length ivory wood was not influenced by temperatures of 25 oC constant and alternating temperature of 20-30 oC, from 90 days of storage. Among provenances, Entre Rios do Oeste stood out from the others to 0 and 360 days when he presented the highest rate of germination. The fruit stored in glass containers in uncontrolled environment and environmental conditions, did not show variations, related to the water content, thus demonstrating the best way to store ivory wood fruit. The mass of a thousand fruits stick ivory were 329.5 g, 585.5 g and 450.0 g for the provenances of Marechal Cândido Rondon, Entre Rios do Oeste and Diamonte D'Oeste, respectively. To seed ivory wood, the constants found to predict longevity were: Ke = 2.8667; Cw = 9.7697 E-013; Ch = 1.3435 E-012 and Cq = 1.1651 E-013. Using the storage conditions with average temperatures of 23 oC or 15 oC, and the ivory wood seeds showing moisture content of 12%, can be stored for up to 2 years. The values of the Pearson correlation between the actual percent germination calculated and the percentage of germination were 73% and 76% for the provenances Entre Rios do Oeste and Diamonte D'Oeste, and 77% and 74% for uncontrolled and controlled environment, respectively